Intestinal ulcers induced by intravesical bacillus Calmette-Guérin therapy. (3rd April 2021) - Tsuchiya, Haruka; Hanata, Norio; Harada, Hiroaki; Shoda, Hirofumi; Fujio, Keishi
Abstract: Intravesical bacillus Calmette-Guérin (iBCG) therapy, one of the established treatments for bladder carcinoma, is known for its association with adverse events, including rheumatic manifestations. We describe the case of a 72-year-old man with synovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO) syndrome who developed inflammatory bowel disease unclassified after iBCG therapy for bladder carcinoma. The critical role of the IL-23/IL-17 axis in the pathogenesis IBD and all the domains of SAPHO syndrome has been reported previously. In the present case, the activation of the IL-23/IL-17 axis, probably due to the disease, could have been exacerbated by iBCG therapy, as observed in mice that received BCG immunotherapy. We suggest that patients with rheumatic diseases on iBCG therapy should be observed carefully since iBCG could be a contributing factor for autoimmune pathology including IBD.